TARGET AND MASTERY LANDS THE SCOPE OF LAND AGRICULTURAL LAND REDISTRIBUTION IN THE PROVINCE OF SOUTH KALIMANTAN - Fathul Achmadi Abby; Diana Rahmawati; Yulia Qamariyanti; Syahrida (Lambung Mangkurat Law Journal, 2017)
:This type of research is juridical-empirical, character of an explanatory study, using non probality sampling technique, with sampling purposive or judgment sampling, with its own considerations for selecting members of the sample. Respondents farmers, farmer groups, informants: National Land Agency, Agency for Agricultural Extension and the National Bureau of Statistics.A redistributionsubject of Agricultural Land in South Kalimantan province, not all poor farmers and sharecroppers, but there are also traders, private employees and civil servants. Due to ignorance of the farming community will Land Redistribution program. Object of agricultural land redistribution in South Kalimantan, only on state land or land uncultivated state-controlled, whereas the maximum limit for the excess land, absentee land and abandoned land is not part of the object of reform because it could not be implemented due to the constraints of data and information not enough about it. Because the object redistribution of agricultural land that is not up to two(2) acres, has not been able to fulfill the lives of farmers, because it is too small farms and agricultural produce is not maximized.